Βιβλιοκρισία:Constantine Porphyrogennetos, The Book of Ceremonies, in 2 volumes. Translated by ANNE MOFFATT and MAXEME TALL, with the Greek edition of the CSHB(Bonn 1829) [Byz. Australiensia 18], Canberra 2012. ISBN:978-1-876503-42-0 - ΛΟΥΓΓΗΣ, Τηλέμαχος (Byzantina Symmeikta, 2014)
Βιβλιοκρισία του: <!--[if gte mso 9]> 1024x768 <![endif]--> Constantine Porphyrogennetos, The Book of Ceremonies, in 2 volumes. Translated by Anne Moffatt and Maxeme Tall, with the Greek edition of the Corpus Scriptorum Historiae Byzantinae (Bonn 1829) [Byzantina Australiensia 18], Canberra 2012. ISBN: 978-1-876503-42-0; ISSN: 0725-3079 <!--[if gte mso 9]> Normal 0 false false false EL X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->